Characterizing the Ordered AG-Groupoids Through the Properties of Their Different Classes of Ideals - Kausar, N.; Munir, M.; Gulzar, M.; Addis, G. M. (KU Publ., 2020)
In this article, we have presented some important charcterizations of the ordered non-associative semigroups in relation to their ideals. We have initially characterized the ordered AG-groupoid through the properties of the their ideals, then we characterized the two important classes of these AG-groupoids, namely the regular and intragregular non-associative AG-groupoids. Our aim is also to encourage the research and the maturity of the associative algebraic structures by studying a class of non-associative and non-commutative algebraic structures called the ordered AG-groupoid.
Реттелген AG-группоидтардың әртүрлі идеалды кластарының қасиеттері бойынша сипаттамасы
Характеризация упорядоченных AG-группоидов через свойства их различных классов идеалов
Keywords: Ordered AG-groupoids; left (right; interior; quasi-; bi-; generalized bi-) ideals; regular (intraregular) ordered AG-groupoids